2004
DOI: 10.1063/1.1771806
|View full text |Cite
|
Sign up to set email alerts
|

Concentration quenching of Eu-related luminescence in Eu-doped GaN

Abstract: The dependence of Europium (Eu)-related luminescence intensity on the Eu concentration in Eu-doped GaN was studied. This luminescence is observed at 622 nm and originates from the intra-4f transition of the Eu 3+ ion. The intensity of the luminescence increased with increasing Eu concentration, up to about 2 at. %, and then abruptly decreased. It was found that polycrystalline growth began to be induced at Eu concentrations of more than 2 at. %. In addition, clear evidence for the formation of EuN compounds wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
53
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 16 publications
2
53
0
Order By: Relevance
“…[1][2][3][4][5][6] In particular, high-quality GaN is one of the most interesting materials to be used as host crystals for impurity doping and GaN films doped with rare-earth ions are promising materials for light emitters in the visible and infrared spectral regions. [7][8][9][10][11] It has been demonstrated that Eu 3+ -doped GaN ͑GaN:Eu 3+ ͒ epitaxial films exhibit highly efficient red luminescence and stimulated emission due to intra-4f transitions of Eu 3+ ions. 10,11 The spatial distribution of the doped Eu 3+ ions in heavily doped GaN : Eu 3+ films may determine the luminescence properties of such films.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…[1][2][3][4][5][6] In particular, high-quality GaN is one of the most interesting materials to be used as host crystals for impurity doping and GaN films doped with rare-earth ions are promising materials for light emitters in the visible and infrared spectral regions. [7][8][9][10][11] It has been demonstrated that Eu 3+ -doped GaN ͑GaN:Eu 3+ ͒ epitaxial films exhibit highly efficient red luminescence and stimulated emission due to intra-4f transitions of Eu 3+ ions. 10,11 The spatial distribution of the doped Eu 3+ ions in heavily doped GaN : Eu 3+ films may determine the luminescence properties of such films.…”
mentioning
confidence: 99%
“…[7][8][9][10][11] It has been demonstrated that Eu 3+ -doped GaN ͑GaN:Eu 3+ ͒ epitaxial films exhibit highly efficient red luminescence and stimulated emission due to intra-4f transitions of Eu 3+ ions. 10,11 The spatial distribution of the doped Eu 3+ ions in heavily doped GaN : Eu 3+ films may determine the luminescence properties of such films. In fact, spectroscopic studies of the photoluminescence ͑PL͒ properties of GaN:Eu 3+ epitaxial films suggest the presence of several Eu sites that give rise to different peaks in PL spectra.…”
mentioning
confidence: 99%
See 3 more Smart Citations